2020
DOI: 10.1093/gbe/evaa082
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of ancV1R as a Predictive Signature for the Loss of Vomeronasal System in Mammals

Abstract: The vomeronasal organ (VNO) plays a key role in sensing pheromonal cues, which elicits social and reproductive behaviors. Although the VNO is highly conserved across mammals, it has been lost in some species that have evolved alternate sensing systems during diversification. In this study, we investigate a newly identified VNO-specific gene, ancV1R, in the extant 261 species of mammals to examine the correlation between genotype (ancV1R) and phenotype (VNO). As a result, we found signatures for the relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The general histology study showed however an apparently developed VNO (Hart et al, 1988). These striking anatomical observations found their genetic correspondence in a recent study of ancV1R gene expression (Zhang & Nikaido, 2020), considered a reliable diagnostic indicator of VNO function. The authors observed the inactivation of ancV1Rs expression in seals, sea otter, giant otter, fossa, the owl monkey, and alcelaphine antelopes.…”
Section: Introductionsupporting
confidence: 62%
“…The general histology study showed however an apparently developed VNO (Hart et al, 1988). These striking anatomical observations found their genetic correspondence in a recent study of ancV1R gene expression (Zhang & Nikaido, 2020), considered a reliable diagnostic indicator of VNO function. The authors observed the inactivation of ancV1Rs expression in seals, sea otter, giant otter, fossa, the owl monkey, and alcelaphine antelopes.…”
Section: Introductionsupporting
confidence: 62%
“…Translating sequencing studies into neuroanatomical terms is not always easy. A recent study on TRPC2 gene regression stated: ‘The results of our present study invite more in‐depth neuro‐anatomical investigation in mammals for which VNO function remains equivocal’ (Zhang and Nikaido, 2020). The high degree of pseudogenisation observed among vomeronasal receptors represents an unresolved issue which could explain the discrepancies observed between sequencing and neuroanatomical studies.…”
Section: Discussionmentioning
confidence: 67%
“…The reduction of V1R s revealed in this study is consistent with the findings of the previously published studies. 67 The inactivation of TRPC2 s 76 , 77 and ancV1R s, 78 , 79 which is responsible for VNO function, suggested the degeneration of VNOs in most bat lineages including megabats. Although most bats do not possess intact V1R s, Parnell’s mustached bat possesses four intact V1R s ( Fig.…”
Section: Resultsmentioning
confidence: 99%